Pengelolaan Populasi Hama Spodoptera exigua Hübner (Lepidoptera; Noctuidae) dengan Tanaman Refugia pada Tanaman Bawang Merah - Ginting, Tri Yaninta; Setiawan, Andi; Aziz, Muhammad Farhan Abdul; Aezad, Muhammad Hafiq (JURNAL AGROPLASMA, 2024)
This study aims to manage the population of Spodoptera exigua pests using refuge plants in onion crops. The research employed a non-factorial randomized complete block design with 4 treatments, namenly P0 (red onion without refuge plants/ control), P1 (red onion intercropped with Marigold), P2 (red onion intercropped with Zinnia), and P3 (red onion intercropped with combination both Marigold and Zinnia), with each treatment being replicated 6 times. The study comprised 24 experimental units, with each unit containing 4 plants, resulting in a total of 96 plants. The results revealed that the highest population density occurred in treatment P0 (red onion without refuge plants/ control) with a percentage of 0.55 %, while the lowest population density was observed in treatment P3 (red onion intercropped with combination both Marigold and Zinnia) with a percentage of 2.1x10-17 %. The analysis indicated significant differences between treatments P0 and P3. The conclusion drawn from this study is that treatment P3, involving the combination of Marigold and zinnia, yielded the most effective results for managing the population of S. exigua pests in red onion cultivation. Keywords: red onion, population, refuge plants, S. exigua